Relationship between Periodontitis and Rheumatoid Arthritis: Review of the Literature - Vilana Maria Adriano Araújo; Iracema Matos Melo; Vilma Lima (Hindawi Limited, 2015)
Periodontitis (PD) and rheumatoid arthritis (RA) are immunoinflammatory diseases where leukocyte infiltration and inflammatory mediators induce alveolar bone loss, synovitis, and joint destruction, respectively. Thus, we reviewed the relationship between both diseases considering epidemiological aspects, mechanical periodontal treatment, inflammatory mediators, oral microbiota, and antibodies, using the keywords "periodontitis" and "rheumatoid arthritis" in PubMed database between January 2012 and March 2015, resulting in 162 articles. After critical reading based on titles and abstracts and following the inclusion and exclusion criteria, 26 articles were included. In the articles, women over 40 years old, smokers and nonsmokers, mainly constituted the analyzed groups. Eight studies broached the epidemiological relationship with PD and RA. Four trials demonstrated that the periodontal treatment influenced the severity of RA and periodontal clinical parameters. Nine studies were related with bacteria influence in the pathogenesis of RA and the presence of citrullinated proteins, autoantibodies, or rheumatoid factor in patients with PD and RA. Five studies investigated the presence of mediators of inflammation in PD and RA. In summary, the majority of the articles have confirmed that there is a correlation between PD and RA, since both disorders have characteristics in common and result from an imbalance in the immunoinflammatory response.